The effect of flow patterns and energy dissipation over stepped chutes on aeration efficiency - Baylar, Ahmet; Unsal, Mehmet; Ozkan, Fahri (Korean Society of Civil Engineers-Ksce, 2011)
Stepped chutes that are commonly used for gabion weirs, river training, irrigation channels, and storm waterways have become popular in recent years mainly due to the intrinsic low-cost and the speed of construction. Stepped chutes are used also for in-stream re-aeration and in water treatment plants to enhance the air-water transfer of atmospheric gases and of volatile organic components. In a stepped chute, the provision of steps can produce significant energy dissipation. This paper seeks the effect of energy dissipation over stepped chutes on aeration efficiency. It is observed from the results that aeration efficiency increases with increasing energyloss ratio. There is higher energy dissipation in nappe flows than skimming flow situations and nappe flow regime lead to greater aeration efficiency than skimming flow regime. Moreover, regression equations are obtained relating aeration efficiency to stepped chute slope and energy-loss ratio. For this aim, genetic expression programming, a recently developed artificial intelligence technique, is used. The model equations obtained have high correlation coefficients and low minimum square error values.
Keywords: aeration efficiency; energy dissipation; oxygen transfer; stepped chute